2022
DOI: 10.3389/fneur.2022.1021536
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow regulation is not acutely altered after a typical number of headers in women footballers

Abstract: BackgroundThe repeated act of heading has been implicated in the link between football participation and risk of neurodegenerative disease, and acutely alters cerebrovascular outcomes in men. This study assessed whether exposure to a realistic number of headers acutely influences indices of cerebral blood flow regulation in female footballers.MethodsNineteen female players completed a heading trial and seated control trial on two separate days. The heading trial involved six headers in 1 h (one every 10 min), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Typically this is accepted when P ET CO 2 is within ~ 8 mmHg of eucapnia (Coverdale et al 2014 ; Verbree et al 2014 ). As is typical during SSM (Smirl et al 2015 , 2022 ; Burma et al 2020a ; Jack et al 2022 ), this was achieved during our dCA assessment, but was exceeded during the hyperventilation protocol. However, our hyperventilation challenge replicated a protocol known to be sensitive to change in the days following a concussive event (Len et al 2011 ), and we observed similar decreases in P ET CO 2 .…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Typically this is accepted when P ET CO 2 is within ~ 8 mmHg of eucapnia (Coverdale et al 2014 ; Verbree et al 2014 ). As is typical during SSM (Smirl et al 2015 , 2022 ; Burma et al 2020a ; Jack et al 2022 ), this was achieved during our dCA assessment, but was exceeded during the hyperventilation protocol. However, our hyperventilation challenge replicated a protocol known to be sensitive to change in the days following a concussive event (Len et al 2011 ), and we observed similar decreases in P ET CO 2 .…”
Section: Discussionsupporting
confidence: 56%
“…A decrease in phase has been observed during SSM following a season of contact sports, and the magnitude of this change was also positively associated with the accumulation of head impact accelerations (Wright et al 2018a ). Interestingly, no changes in phase have been observed after 6 headers, despite replicating the study design and dCA methodology (Jack et al 2022 ). The correlation between head impacts received and the change in dCA phase observed here suggests that a greater number of headers may have elicited such alterations.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations